2017
DOI: 10.1007/s11356-017-8443-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental and anthropogenic factors at the bottom sediments in a Doce River tributary in Brazil

Abstract: In developing countries, it is uncommon to find watersheds that have been the object of detailed environmental studies. It makes the assessment of the magnitude of environmental impacts and pollution of these sites difficult. This research demonstrated ways to understand the dynamics of river bottom sediments contamination, even for watersheds with a lack of environmental data. Based on geochemical affinity, we conducted a comprehensive study on the concentration of metals and metalloids. Then, we discussed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 19 publications
0
5
0
3
Order By: Relevance
“…However, in this study, only the Zn concentrations on weekdays significantly increased. The elevated Zn concentrations could be originated from agricultural runoff, [ 43–45 ] road runoff, [ 46 ] traffic emissions, and atmospheric deposition, [ 1,47,48 ] as well as natural occurrences, [ 49 ] industrial, [ 20,44,50 ] and mining activities. [ 22,23,51 ] The increased Zn may come from point sources because the survey was undertaken in clear weather (no runoff discharges).…”
Section: Resultsmentioning
confidence: 99%
“…However, in this study, only the Zn concentrations on weekdays significantly increased. The elevated Zn concentrations could be originated from agricultural runoff, [ 43–45 ] road runoff, [ 46 ] traffic emissions, and atmospheric deposition, [ 1,47,48 ] as well as natural occurrences, [ 49 ] industrial, [ 20,44,50 ] and mining activities. [ 22,23,51 ] The increased Zn may come from point sources because the survey was undertaken in clear weather (no runoff discharges).…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al investigated 10 large-scale pig farms that digested piggery wastewater in China and found that Cu is detectable in all farms, and its concentrations reached the discharge limit of 0.5 mg/L. Dos et al also reported that unsustainable agriculture and livestock result in high concentrations of Cu (464.7 mg/kg) in a Doce River tributary in Brazil.…”
Section: Copper and Environmentsmentioning
confidence: 99%
“…Além da orientação dos valores referencias geoquímicos, outra maneira de verificar a origem dos metais e dos semimetais é usar a classificação de Goldschmidt (1923). Essa classificação agrupa elementos por afinidades geoquímicas e permite verificar se a gênese desses elementos reflete a influência da litologia regional ou a interferência antropogênica (Dos Reis et al, 2017). Essa classificação segue o princípio de que alguns dos minerais, em processo de desagregação, liberam elementos químicos em quantidades similares.…”
Section: Na Região Dos Municípios Deunclassified